The impact of portal vein tumor thrombus on long-term survival after liver resection for primary hepatic malignancy. Issue 7 (July 2020) - Zhang, Fan; Lu, Chong-De; Zhang, Xiu-Ping; Chen, Zhen-Hua; Zhong, Cheng-Qian; Hu, Yi-Ren; Wei, Xu-Biao; Zhou, Bin; Wang, Kang; Chai, Zong-Tao; Wu, Meng-Chao; Lau, Wan Y.; et al.
Abstract: Background: The aim of this study was to evaluate the effect of portal vein tumor thrombus (PVTT) on the prognosis of patients undergoing liver resection (LR) for primary liver malignancies (PLC). Methods: The recurrence-free survival (RFS) and overall survival (OS) for patients undergoing LR with and without PVTT for three primary liver malignancies, including hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC) and hepato-cholangio carcinoma (CHC) were compared using the Kaplan-Meier method and Cox regression analysis. Results: In total, 3775 patients with PLC who underwent LR were included in this study. The incidence of PVTT in patients undergoing LR with HCC, IHC and CHC were 46%, 20%, and 17%, respectively. The median RFS and OS were significantly better for patients with HCC as compared to ICC or CHC (16 vs 11 vs 13 months; 21 vs 16 vs 18 months, respectively; P < 0.001). However, the presence of PVTT resulted in similarly poor RFS and OS in these 3 subgroups of patients (9 vs 8 vs 8 months, P = 0.062; 14 vs 13 vs 12 months, respectively, P = 0.052). Conclusion: Although the prognosis of patients with PLC varied by histological subtype, once PVTT occurred, survival outcomes after LR were similarly poor across all three subgroups.